2016
DOI: 10.1159/000448694
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/Phenotype Analysis in 67 Chinese Patients with Gitelman's Syndrome

Abstract: Background: Gitelman's syndrome (GS) is an autosomal recessive renal tubular disorder, which is caused by the mutations in SLC12A3. This study was designed to analyze the characteristics of the genotype and phenotype, and follow-up in the largest group of Chinese patients with GS. Methods: Sixty-seven patients with GS underwent SLCl2A3 analysis, and their clinical characteristics and biochemical findings as well as follow-up were reviewed, aiming to achieve a better description of GS. Additionally, the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
5
28
3
Order By: Relevance
“…Therefore, for some patients with a poor effect of potassium supplementation, we can try to increase the dosage of magnesium supplementation. Previous studies reported that spironolactone might be helpful for hypokalemia to some degree, and spironolactone combined with potassium supplements tended to be more effective [ 22 , 23 ], but we did not find an advantage of spironolactone treatment. During follow-up, one GS patient developed IFG and two patients presented proteinuria.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Therefore, for some patients with a poor effect of potassium supplementation, we can try to increase the dosage of magnesium supplementation. Previous studies reported that spironolactone might be helpful for hypokalemia to some degree, and spironolactone combined with potassium supplements tended to be more effective [ 22 , 23 ], but we did not find an advantage of spironolactone treatment. During follow-up, one GS patient developed IFG and two patients presented proteinuria.…”
Section: Discussioncontrasting
confidence: 92%
“…We found four recurrent mutants in SLC12A3, which would provide significant information for the screening and genetic counseling of GS. Consistent with our study, Shao, Tseng and Liu et al also considered the missense mutations T60M and D486 N as highly frequent mutations in the Chinese population [ 8 , 23 , 29 ]. Although GS is inherited in an autosomal recessive manner, up to 30% of patients have simple heterozygous mutations [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We believe this work would facilitate a better understanding of the pathogenesis for GS. In addition, patients with multiple mutations (≥3 mutations) observed in our study (10.9%) were also reported by other studies with a proportion of 6.0% to 12.0% ( 4,33,34 ). Since part of the mutations are classified as “uncertain significance” based on current data without functional studies, more in vitro or in vivo functional studies are needed to help provide evidence and disclose the genetic disorder for the multiple mutations.…”
Section: Discussionsupporting
confidence: 90%
“…No other signi cant difference was detected in the clinical parameters evaluated in this study. However, some authors have already demonstrated that the hypokalemia is more di cult to be corrected in BS type 3 than BS type 1 or type 2 [37][38][39].…”
Section: Discussionmentioning
confidence: 99%